Metabolism Balance Regulation via Antagonist‐Functionalized Injectable Microsphere for Nucleus Pulposus Regeneration. (28th September 2020) - Xu, Yichang; Gu, Yong; Cai, Feng; Xi, Kun; Xin, Tianwen; Tang, Jincheng; Wu, Liang; Wang, Zhen; Wang, Fei; Deng, Lianfu; Pereira, Catarina Leite; Sarmento, Bruno; et al.
Abstract: Antagonist therapy represents a potential treatment for extracellular matrix (ECM) metabolic imbalance via the specific binding of inflammatory factors resulting from inflammation. However, the short half‐life of antagonist bioactivity creates challenges for their clinical application. Herein, bovine serum albumin nanoparticles (BNP) encapsulating recombinant human soluble tumor necrosis factor (TNF) receptor type II (rhsTNFRII) are grafted onto microfluidic poly(l ‐lactic acid) (PLLA) porous microspheres through chemical bonds, constructing antagonist‐functionalized injectable porous microspheres (MS‐BNP) for in situ injection into the nucleus pulposus (NP), aimed at regulating the metabolic balance of ECM, thus inhibiting intervertebral disc degeneration. Several binding sites within the BNPs improve encapsulation efficiency, promote the sustained release of rhsTNFRII, and regulate ECM metabolism in the NP. Moreover, PLLA porous microspheres display excellent injectability and porosity and demonstrate efficient and uniform loading of nanoparticles through chemical grafting. By delivering MS‐BNP into the NP, a suitable environment is created in situ. Immunohistochemical analysis at 4 and 8 weeks shows that compared with other experimental groups, the expression of TNF‐α is significantly inhibited for 6.11–15.65 folds and 4.59–22.14 folds, respectively, and a significant regeneration in NP occurred. This work proposes a novel porous microsphere therapy functionalized by antagonist molecules for the treatment of ECM metabolic disorders, caused by chronic inflammatory responses. Abstract : Inspired by the inflammation of the intervertebral disc degeneration microenvironment, antagonist‐functionalized injectable porous microspheres capable of modulating inflammation responses and regulating extracellular matrix metabolism balance was designed to satisfy the specific demand for early‐stage restoration of the intervertebral disc microenvironment and its regeneration.